Organizations in Times of Uncertainty: from Safety to Contingency - Pont Vidal, Josep (Revista del CLAD Reforma y Democracia, 2021)
Contingency emerges in contemporary societies as the possible present and with associated attributes such as risk, insecurity and danger. This affects society as a whole, organizations, and the logic in which decisions are made. This paper starts from the assumption of the existence of paradoxes and limits of instrumental rationality in decision-making that emerge in this contingent scenario. In the current period of insecurity and risk, transformations in organizations must take into account the conditions presented by contingency. The analysis is limited to the disciplinary field of the sociology of organizations and, particularly, to the study related to rationality in decision-making. The explanation is articulated into two sections. On the conceptual and analytical level, the changes taking place in organizations are analyzed on the basis of two substantive variables: 1) the process of modification of Weberian instrumental rationality and bounded rationality based on the rationalist conception of the decision and structured with a linear multivariable logic and in a security context; and 2) the process in which the new contingent context associated with uncertainty, risk and danger, influences the logic of instrumental rationality. The result of this double process, according to the thesis presented, is the emergence of a new type of rationality called rationality in contingency, based on multiple causality, on an inevitable situation that happens for some reason, and with an open future of possibilities. For organizations it means a transformation into a type of rationality called contingent rationality. An outline of an exploratory model of analysis based on ecological systems and contingency is presented.